Renewing the Colonial Past: Slavery and Modernity in the Raul Bopp’s Urucungo - da Cunha, Yasmeen Pereira; Jubé Júnior, Miguel d’Abadia Ramos (Pontifícia Universidade Católica de São Paulo, 2019)
Based on the assumptions of Marxist aesthetics, this article presents an analysis of the poems “Diamba,” “Mucama” and “Favela no. 2” from the book Urucungo (1932) by Raul Bopp in an attempt to show how the aesthetic form of those poems represents the social process of black slavery in Brazil up until the liberation of slaves and their rise in the capitalist class society. It demonstrates the relationship between literary form and social content, mainly in the configuration of the lyrical subject who narrates the history of the African black on Brazilian territory from the perspective of the oppressed. For that purpose, the lyrical subject moves along a historiographic path that demonstrates that the colonial past is renewed in the present, resulting in the oppression of blacks even after the abolition of slavery.